Etyczny bunt w reżimie demokratycznym - Baluch, Michał (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
After twenty years of a democratic regime in Poland, one can see its condition. There are three categories of a riot - “the narrowest”, “narrow” and “wide”. The articele presents the examples of each type and the cause of their existence. Sometimes it results from the fasion or the reality is somehow changed. These changes may be fragmentary or they may affect the whole society. The article discusses this differentiation. To become a rebel, many obstacles must be overcome.